House ownership financing: sharia economic perspective - Harefa, Safaruddin (Journal of Islamic Economics Management and Business (JIEMB), 2021)
A place to live is one of the basic needs, so everyone tries to have it. However, people often have difficulty buying them in cash due to increasingly expensive house prices and limited funds. From here, banking institutions offer a house ownership model through a credit system. This article aims to determine the position of house ownership financing/credit from an Islamic economic perspective and what contracts can be made in this financing. This study uses a normative juridical method. Research data is obtained through library data in books, journals, laws and regulations, and other scientific writings related to mortgages from an Islamic economic perspective. Data analysis used qualitative data analysis methods, which were then presented descriptively. The study results that based on sharia economics, reinforced by the fatwa of the National Sharia Board-Indonesian Council of Ulama, financing home ownership in Islamic economics is justified as long as it complies with sharia provisions. Some of the contracts that can be made in financing the ownership of the house include murābaḥah, ijārah muntahiya bi tamlīk, istiṣnā‘, and mushārakah mutanāqiṣah contracts.